Avaliação Do Desempenho Docente Nas Redes Públicas Estaduais De Ensino Do Brasil E Sua Relação Com A Remuneração - Zatti, Antonio Marcos [UNIFESP] (2017)
The aim of this study is to outline the Brazilian panorama related to the evaluation of the work of teaching staff linked to the payment of bonus, in all states and in the Federal District, in force in 2015. It seeks to identify the characteristics and main trends of these policies, implemented in general under the justification of the raise of value of basic education and its teachers, relating the results of evaluation and the work of teachers. The research is linked to a Project called Teaching Personnel Payment Observatory (Pord), funded by Capes since 2008. To identify the current norms related to these processes, research was carried out on institutional sites of all Brazilians states, as well as sending correspondence to these organizations, requesting the regulations in force. In 14 Brazilian statesthe evaluation of the performance of the bonus related to the teaching staff in payment was identified - Acre, Amazonas, Bahia, Ceará, Espírito Santo, Goiás, Minas Gerais, Paraíba, Paraná, Pernambuco, Rio de Janeiro, Rio Grande do Sul, São Paulo and Tocantins. By means of documentary analysis and treatment of qualitative and quantitative data, the understanding of these policies was made considering fundamentally the concepts of technological rationality and the principle of performance elaborated in works of Herbert Marcuse. Moreover, the interpretation on the consequences of this evaluative strategy was based on the concept of individualization, identified by Robert Castel in labor relations. In face of a reality governed by the principle of performance and the constant pursuit of productivity, evaluation policies, instead of being strategies that promote the valorization of the professional category, were constituted as technologies of control over the work of teachers, establishing patterns of behavior, requiring adaptation to the logic of technological rationality. As effect, a reconfiguration of labor relations and the progressive tendency towards the individualism and the responsibility of the subjects were observed.